2003
DOI: 10.1046/j.1439-0485.2003.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in the Covering Behaviour of the Shallow Water Sea Urchin Paracentrotus lividus

Abstract: Abstract.  A number of recent field‐based studies have investigated the possible functions of covering behaviour in a range of echinoid species. Some of these have found important relationships between covering behaviour and environmental factors, such as light (in particular, ultra‐violet light) and covering item availability. However, these studies have often shown considerable within‐species variation, thus making covering functionality both within and between species difficult to interpret. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Its spatial distribution can vary on both small and large scales in relation to the interaction of abiotic and biotic factors (Boudouresque and Verlaque 2001). For example, the variability of water temperature and solar radiation can partially explain intraspecific variation in covering behaviour type in P. lividus (Crook 2003). The heterogeneity of the substratum plays a key role in providing P. lividus with shelter, thus influencing the structuring of populations, where predation pressure (which includes human harvesting) is particularly high (Bonaviri et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Its spatial distribution can vary on both small and large scales in relation to the interaction of abiotic and biotic factors (Boudouresque and Verlaque 2001). For example, the variability of water temperature and solar radiation can partially explain intraspecific variation in covering behaviour type in P. lividus (Crook 2003). The heterogeneity of the substratum plays a key role in providing P. lividus with shelter, thus influencing the structuring of populations, where predation pressure (which includes human harvesting) is particularly high (Bonaviri et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Glyptocidaris urchins, for example, were found to most likely heap for mechanical defense, and their place in the phylogeny suggests that this may be the ancestral reason for sea urchin crypsis (Figure 3). However, the effects of light intensity or the presence of predators have not been studied Strongylocentrotus urchins [7,19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for crypsis and the extent to which it is seen differs widely between species [14]. However, the behavior is also affected by size and mobility [19] as well as the energetic cost of covering [20]. It is possible, then, that the differences in the covering reaction between species are due to variations in animal size and mobility as well as energetic costs, rather than genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Covering behavior, which is exhibited in species from both shallow (Verling et al, 2002) and deep (Pawson and Pawson, 2013) environments, refers to sea urchins using their tube feet and spines to move objects, such as shells, stones and algae fragments, onto their dorsal surface. A number of hypotheses have been tested to explain the evolutionary drives of covering behavior (Crook, 2003), including protection against exposure to solar radiation (Adams, 2001;Kehas et al, 2005;Dumont et al, 2007;Sigg et al, 2007), predation (Amsler et al, 1999;Agatsuma, 2001), desiccation (Orton, 1929), wave surge (Millott, 1976) and fl oating sand (Richner and Milinski, 2000), or/and as a refl exive action (Dambach and Hensel, 1970;Lawrence, 1976). Although it is considered that covering behavior is a behavioral avoidance strategy against UV radiation (Lamare et al, 2011), the fi tness benefi ts of this behavior remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation analysis is an important approach to investigating the fi tness basis of animal behaviors. Among the six hypotheses of potential functions of this behavior (Crook, 2003), protection against suspended sand is of particular interest. Richner and Milinski (2000) reported that covering behavior was signifi cantly enhanced in the sea urchin Paracentrotus lividus during exposure to suspended sand.…”
Section: Introductionmentioning
confidence: 99%